2021
DOI: 10.1098/rsos.210354
|View full text |Cite
|
Sign up to set email alerts
|

Two different synchronous spectrofluorimetric approaches for simultaneous determination of febuxostat and ibuprofen

Abstract: Two green, simple and sensitive synchronous spectrofluorimetric methods were developed for the first time for the simultaneous estimation of febuxostat (FEB) and ibuprofen (IBU). Method I is constant-wavelength synchronous spectrofluorimetry where FEB and IBU were recorded at 329 and 258 nm, respectively, using Δ λ of 40 nm. Method II is constant-energy synchronous spectrofluorimetry using a wavenumber interval of −4000 cm −1 . All measurements were carried out i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…It is observed that at Δλ = 35 nm, only BSA (25 μM) showed a fluorescence emission peak at 318 nm, whereas only ibuprofen (100 μM) showed two SFS emission peaks at 364 and 353 nm (Figure d). The blue shift in the maximum emission peak of SFS of BSA from normal fluorescence emission spectra is due to the fact that Stokes shift (for BSA ∼60 nm) is greater than Δλ value (35 nm) used in SFS, whereas for ibuprofen, the SFS maximum emission peaks are red-shifted as compared to the normal fluorescence emission peak because the Stokes shift (for ibuprofen ∼30 nm) is smaller than SFS Δλ. With the increase in the concentration of ibuprofen (from 0 to 100 μM), it is found that the peak at 318 nm (corresponding to BSA) is quenched, whereas the intensities of the two peaks at 353 and 364 nm (corresponding to ibuprofen) are enhanced.…”
Section: Resultsmentioning
confidence: 96%
“…It is observed that at Δλ = 35 nm, only BSA (25 μM) showed a fluorescence emission peak at 318 nm, whereas only ibuprofen (100 μM) showed two SFS emission peaks at 364 and 353 nm (Figure d). The blue shift in the maximum emission peak of SFS of BSA from normal fluorescence emission spectra is due to the fact that Stokes shift (for BSA ∼60 nm) is greater than Δλ value (35 nm) used in SFS, whereas for ibuprofen, the SFS maximum emission peaks are red-shifted as compared to the normal fluorescence emission peak because the Stokes shift (for ibuprofen ∼30 nm) is smaller than SFS Δλ. With the increase in the concentration of ibuprofen (from 0 to 100 μM), it is found that the peak at 318 nm (corresponding to BSA) is quenched, whereas the intensities of the two peaks at 353 and 364 nm (corresponding to ibuprofen) are enhanced.…”
Section: Resultsmentioning
confidence: 96%
“…Various organized media were evaluated for their potential capability to enhance the fluorescence characteristics of PHL and EPH by using concentrations greater than their critical micelles concentrations 45 , 46 . The investigated organized media included macromolecules such as carboxymethyl cellulose, and β-cyclodextrin, as well as surfactants such as tween-80, sodium dodecyl sulfate, and cetrimide.…”
Section: Resultsmentioning
confidence: 99%
“…Although spectrofluorimetric technology is known for its great sensing properties, selectivity issues might occur when studying multi-component combinations due to the overlay of broadband spectra. This overlaying difficulty might be confronted by the employing synchronous technique, as it has several of benefits over standard fluorescence techniques, which include high selectivity, proper spectra, and minimum intrusion [34][35][36] . SFS is highly basic but proved to be an effective approach for the quantitative assessment of the two drugs in an appropriate time frame because of its narrow and sharp spectra [37][38][39][40] .…”
Section: Simultaneous Spectrofluorimetic Determination Of Remdesivir ...mentioning
confidence: 99%